The role of learning organization in enhancing the implementation of national dual training system (NDTS) in Malaysia - Spahat, Ghalip (2011)
The establishment of Learning Organisation (LO) practices in the Department of Skills Development (DSD) is significant in term of providing the necessary impetus for the implementation of National Dual Training System (NDTS). Within DSD the initiative will greatly foster its Enculturation of learning, procedure of learning, strengthen leadership capabilities for learning, enforce good policy for learning, establish the learning processes and ICT utilization for learning. Thus the purpose of this study is to investigate the significant variables that contribute to the level of LO practice (organizational performance in NDTS), to measure the relationships between the variables, to identify the level of LO practice in DSD and to propose improved method for the enhancement of NDTS implementation. This research design is categorised under the descriptive quantitative research, using survey, interview and structured questionnaires. Questionnaire forms were distributed to 111 out of the total of 250 DSD officers and 3 subject matter experts were interviewed. Frequency test, mean test, ANOVA test, Spearman‟s rho test, Multiple Linear Regression, G-Power test and factor analysis test were used to measure the inter-relationships between the variables and the level of LO practice in DSD. This research found that only 52.3% of the respondents perceived that LO practices level that enhance NDTS practice, is fairly satisfactory. This implies that the practice of LO in DSD needs to be further intensified. The research also confirmed that the level of LO practices are related with Enculturation of learning, Procedure of learning, Leadership capabilities development, Policy enforcement, Work processes, and ICT utilization. Apart from that, Enculturation of learning and, Procedure of learning and knowledge management are found to the two (2) significant predictors of the LO practices (organizational performance in NDTS). Consequently the level of LO practice in DSD could potentially enhance its functions through its active role in the enculturation and, procedure of learning and knowledge management. The value of Adjusted R Square of 0.427 indicates that Enculturation and procedure of learning and knowledge management contribute 42.7% variance in the level of LO practices that enhance NDTS. Finally the Model of the Roadmap for the Development of LO in DSD is developed to enhance NDTS implementation so that DSD can transform itself into an agile Learning Organization to meet the demands of the twenty-first century.